The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/healthcare10020180
|View full text |Cite
|
Sign up to set email alerts
|

Screening for ADHD Symptoms among Criminal Offenders: Exploring the Association with Clinical Features

Abstract: Background: Attention-deficit/hyperactivity disorder (ADHD) is a disabling disorder. High rates of ADHD have been consistently reported among prisoners. The main objectives were (1) to estimate the prevalence of ADHD symptoms in a sample of male inmates and (2) to investigate the relationship between ADHD symptoms and socio-demographic/clinical features. According to the high prevalence of childhood trauma among inmates, we assessed whether exposition to childhood trauma can be related to the presence of ADHD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Of the 32 studies comparing the prevalence of comorbid psychiatric disorder between subjects with and without adult ADHD, according to our classification criteria, 11 studies involved general populations, 18 studies included psychiatric populations, and three studies focused on incarcerated populations. One of the three studies dealing with incarcerated populations involved only female inmates [23], and the other one study involved only male inmates [24].…”
Section: Plos Onementioning
confidence: 99%
“…Of the 32 studies comparing the prevalence of comorbid psychiatric disorder between subjects with and without adult ADHD, according to our classification criteria, 11 studies involved general populations, 18 studies included psychiatric populations, and three studies focused on incarcerated populations. One of the three studies dealing with incarcerated populations involved only female inmates [23], and the other one study involved only male inmates [24].…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, information for other variables were lacking, including mean monthly dosage for each LAI antipsychotic, reasons for prescribing LAI antipsychotics, previously administered antipsychotic medications (including the type of previous LAI antipsychotic), age at onset, duration of illness and the presence of other comorbid psychiatric diagnoses (Barbui et al ., 2020; Pelizza et al ., 2022; Auxilia et al ., 2023). Nevertheless, other factors that may be associated with the type of prescribed LAI antipsychotic, including migration (Bani-Fatemi et al ., 2019), living in rural or urban communities (Teplin, 1990; Peritogiannis et al ., 2023) and comorbid neurodevelopmental disorders (such as autism spectrum disorder and attention deficit-hyperactivity disorder) (Iasevoli et al ., 2020; Capuzzi et al ., 2022) were not evaluated in this study for lack of reliable information. Fifth, most of the data is based on self-report, increasing the risk of recall bias and skewed self-presentation.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Cupertino et al [ 58 ] reported that the G allele of rs2251214 may be related to an earlier onset of impairment due to ADHD symptoms, higher incidence of behavioral problems, and comorbid antisocial personality disorder. Nevertheless, it is noteworthy that personality disorders may be predictors of poor outcomes in ADHD and limited response to MPH [ 5 , 59 ]. Thus, we cannot completely exclude a shared genetic risk factors among ADHD and personality disorders, which are, in turn, associated with poor outcomes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies regarding the long-term prognosis of adult ADHD patients are lacking. Further studies with larger samples, taking into account the three presentations of the disorder (predominantly inattentive, predominantly hyperactive-impulsive, and combination) and other environmental or biological factors are needed to have a complete overview of this topic [ 5 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation